2020
DOI: 10.1007/s00109-020-01916-9
|View full text |Cite
|
Sign up to set email alerts
|

Microglial-specific depletion of TAK1 is neuroprotective in the acute phase after ischemic stroke

Abstract: Transforming growth factor-β-activated kinase 1 (TAK1) is upregulated after cerebral ischemia and contributes to an aggravation of brain injury. TAK1 acts as a key regulator of NF-ΚB and the MAP kinases JNK and p38 and modulates post-ischemic neuroinflammation and apoptosis. Microglia are the main TAK1-expressing immunocompetent cells of the brain. However, little is known about the function and regulation of microglial TAK1 after cerebral ischemia. Tamoxifen-dependent conditional depletion of TAK1 in microgli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…The latter are regulated by the mitogen-activated protein kinase kinase kinase (MAP3K) TGFβ-activated kinase 1 (TAK1). TAK1 is highly abundant in the brain and predominantly expressed in microglial cells [20]. It controls viability and inflammation through multiple downstream effectors including MAP kinases p38 and JNK, as well as the transcription factor NF-κB [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter are regulated by the mitogen-activated protein kinase kinase kinase (MAP3K) TGFβ-activated kinase 1 (TAK1). TAK1 is highly abundant in the brain and predominantly expressed in microglial cells [20]. It controls viability and inflammation through multiple downstream effectors including MAP kinases p38 and JNK, as well as the transcription factor NF-κB [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It controls viability and inflammation through multiple downstream effectors including MAP kinases p38 and JNK, as well as the transcription factor NF-κB [21][22][23][24]. Various stimuli including Toll-like receptor 4 (TLR4), TNF-α, IL-1β as well as hypoxia/ischemia have been shown to upregulate and activate TAK1 [20,23,25,26]. While activation of TAK1 is reported to exacerbate brain damage, pharmacological inhibition of TAK1 using 5Z-7-Oxozeaenol exerts neuroprotection after subarachnoid hemorrhage as well as cerebral ischemia [23,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β, a cytokine with multiple functions, regulates inflammatory response following injury in the brain [ 43 ]. Meanwhile, TGF-β activated kinase 1 (TAK1) correlates with the aggravation of injury [ 44 ], and contributes to an inferior long-term stroke outcome via microglial and macrophage responses [ 45 ]. Additionally, PPI with target genes of 67 hub DE-miRNAs emphasized eleven hub genes, i.e., CDC27, SMURF1, RPS21, AREL1, BTBD6, FBXO9, KLHL25, PIK3CB, TRIM71, UBE2R2, and ZNRF2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that microglia plays a pro-in ammatory and pro-apoptotic role in the early stage of I/R [16], which regulating immune response and affecting neuronal function. Microglia works in the early stage of ischemia-reperfusion through morphological changes and secretion of in ammatory factors [17].…”
Section: Discussionmentioning
confidence: 99%